Estrutura de capital, performance ESG, controle estatal e mercados regulados: uma abordagem nacional e regional - Silva, Sônia Fernanda de Sousa (2025)
Contextualization: Studies on corporate capital structure involve decisions about the composition of financing required for their operations and growth. In the current context, both internationally and domestically, there is increasing emphasis on decisions that not only aim for financial outcomes but also integrate practices that contribute to sustainable development, including environmental, social, and governance (ESG) actions. This trend reflects the growing demand for corporate management that combines economic efficiency with a commitment to social and environmental responsibility. Moreover, studying the capital structure of regulated companies is essential to understanding how regional, economic, and institutional factors shape their financial decisions. These companies, often originating from the privatization of former state-owned enterprises, operate in strategic sectors such as energy, telecommunications, and infrastructure, and are subject to regulatory influence. Across different regions, these companies face specific challenges that impact their capital structure, including the availability of financing, economic stability, and governmental policies. Objective: The objective of this study is to investigate the relationship between capital structure and ESG performance, along with its pillars, as well as the influence of state control over Brazilian companies. Additionally, the research examines variables that may impact the capital structure of companies operating under regulatory regimes, considering regional particularities. The study aims to understand how these specific factors influence the capital composition of firms, seeking to explore the relationship between sustainable practices, state control, regulatory characteristics, and regional contexts in capital structuring. Method: In the first essay, the sample consisted of 115 Brazilian non-financial companies with shares traded on B3 and available ESG performance data for the period from 2010 to 2023. The data were obtained from the Thomson Reuters and Economática platforms and analyzed using Percentile Regression. In the second essay, the sample included Brazilian non-financial, regulated companies with shares traded on B3, covering the same period from 2010 to 2023. The data were extracted from the Economática platform and analyzed using panel data regression and Percentile Regression. Results: The main findings of the study on the relationship between capital structure, ESG performance, and state ownership revealed a positive association between the ESG score and its pillars with accounting-based leverage, as well as between the ESG pillars and marketbased leverage. Conversely, ESG performance exhibited a negative relationship with marketbased leverage. Additionally, the impact of state ownership varied across the models analyzed, both in relation to accounting-based and market-based leverage. In the study on the determinants of capital structure in regulated firms, quantile regression was employed to assess the influence of various factors. The results indicated that general liquidity, volatility, and sector consistently showed significance across the three tested models, exhibiting linear behavior. Among these variables, volatility demonstrated a positive relationship with leverage, suggesting that the regulated environment may facilitate resource acquisition by firms, even in the face of revenue fluctuations. In contrast, the variables size and region displayed varying relationships depending on the type of leverage (short-term, long-term, or total) and the percentile analyzed. This highlights distinct responses to different levels and types of leverage, reflecting specific dynamics tied to debt composition. Furthermore, the results emphasized the importance of firm-level characteristics, as well as the significant influence of the sector of activity and the mesoregions of Triângulo Mineiro, Alto Paranaíba, and Sul de Goiás. These variables had a notable impact on short-term, long-term, and total leverage, reinforcing the relevance of regional and sectoral factors in shaping the capital structure of regulated firms. Adherence to the PPGAdm's (Regionality and Management) area of concentration and research line: This study aligns with the concentration area of the Program and its research line by investigating the relevance of factors associated with capital structure and the alignment with ESG performance policies in promoting sustainable business development. Additionally, it seeks to understand the determinants of capital structure within the regulatory context, delving into management practices in specific activity sectors. Regarding regionality, the research examines regional influences on the management of regulated companies, conducting a comparative analysis of the determinants of capital structure for companies located in Triângulo Mineiro, Alto Paranaíba, Sul de Goiás, and other regions of Brazil. This analysis provides insights for more tailored management approaches, considering the economic and institutional specificities of each region. Impact and Innovative Aspect in Intellectual Production: The research stands out by exploring the interactions between relevant topics, such as the relationship between the ESG score and its pillars with corporate capital structure, while also examining the impact of state control on these decisions. Additionally, it introduces an innovative approach by analyzing the determinants of capital structure in companies operating in environments subject to specific regulatory restrictions and influences, comparing them with those located in Triângulo Mineiro, Alto Paranaíba, and Sul de Goiás, as well as other regions. Economic, Social, and Regional Impact: Companies that adopt sustainable practices have the potential to positively impact local well-being, contributing to improvements in environmental, social, and corporate governance aspects. Moreover, region-specific studies can provide valuable insights for planning tailored policies aimed at job creation and regional development. Regional Implications: By identifying the regional particularities that influence capital structure, the study can guide the formulation of more effective public policies and business strategies tailored to local needs. Considering that the research focuses on companies under regulatory regimes, this information enables the development of plans that account for the specific economic and social characteristics of each region. Additionally, by analyzing the relationship between capital structure and ESG practices, the study provides a foundation for initiatives aimed at improving environmental and social conditions in the region. In this way, it contributes to fostering economic growth and job creation in alignment with sustainable development goals. Sustainable Development Goals Addressed by the Research: This study contributes to several of the goals outlined in the 2030 Agenda, including: (SDG 8) Promote sustained, inclusive, and sustainable economic growth, full and productive employment, and decent work for all; (SDG 9) Build resilient infrastructure, promote inclusive and sustainable industrialization, and foster innovation; (SDG 16) Peace, justice, and strong institutions; and (SDG 17) Strengthen the means of implementation and revitalize the global partnership for sustainable development.